IMPACT OF ELEVATED CO2 LEVEL ON GROWTH, TUBER YIELD AND MINERAL CONTENT OF INDIAN POTATO CULTIVARS - Kumar, Prince (Potato Journal, 2019)
The concentration of atmospheric CO2 is constantly increasing and is estimated to exceed 700 ppm by the end of 21st century. Increased CO2 level is likely to affect growth, yield and nutrient acquisition. Thus in the present study effect of elevated CO2 was studied in two potato varieties in transparent walled open-top chambers (OTCs) with ambientÂ ppm) and elevated CO2 levels (550 and 700 ppm) during rabi season of 2015-16. Kufri Surya was found more responsive to elevated CO2 levels than Kufri Pukhraj. At 550 ppm CO2 level the tuber yield increased by 5 per cent in Kufri PukhrajÂ to 38 per cent in Kufri Surya. However, at 700 ppm CO2 level the increase in tuber yield was much higher ranged from 24 per cent in Kufri Pukhraj to 70 per cent in Kufri Surya. Net photosynthesis rate was higher at higher CO2 concentration inÂ both the varieties. Total biomass on dry basis was also significantly higher under elevated CO2 level compared to ambient. Elevated CO2 did not have any significant effect on nutrient (NPK) concentration in tubers.